MuRF1 mono-ubiquitinates TRα to inhibit T3-induced cardiac hypertrophy in vivo - Wadosky, Kristine M (J Mol Endocrinol, 2016)
Thyroid hormone (TH) is recognized for its role in cellular metabolism and growth and participates in homeostasis of the heart. T3 activates pro-survival pathways including Akt and mTOR. Treatment with T3 after myocardial infarction is cardioprotective and promotes elements of physiological hypertrophic response after cardiac injury. Although T3 is known to benefit the heart, very little about its regulation at the molecular level has been described to date. The ubiquitin proteasome system (UPS) regulates nuclear hormone receptors such as estrogen, progesterone, androgen, and glucocorticoid receptors by both degradatory and non-degradatory mechanisms. However, how the UPS regulates T3-mediated activity is not well understood. In this study, we aim to determine the role of the muscle-specific ubiquitin ligase muscle ring finger-1 (MuRF1) in regulating T3-induced cardiomyocyte growth. An increase in MuRF1 expression inhibits T3-induced physiological cardiac hypertrophy, whereas a decrease in MuRF1 expression enhances T3’s activity both in vitro and in cardiomyocytes in vivo. MuRF1 interacts directly with TRα to inhibit its activity by posttranslational ubiquitination in a non-canonical manner. We then demonstrated that a nuclear localization apparatus that regulates/inhibits nuclear receptors by sequestering them within a subcompartment of the nucleus was necessary for MuRF1 to inhibit T3 activity. This work implicates a novel mechanism that enhances the beneficial T3 activity specifically within the heart, thereby offering a potential target to enhance cardiac T3 activity in an organ-specific manner.